Effect of broiler breeder age on pancreas enzymes activity and digestive tract weight of embryos and chicks - Maiorka, A; Santin, E; Silva, AVF; Routman, KS [UNESP]; Pizauro Jr., JM [UNESP]; Macari, Marcos [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2004)
A study was carried out to evaluate the effect of broiler breeder age on the development of the digestive tract of embryos and chicks. Fertilized eggs Cobb from 30 and 60 week-old broiler breeder was utilized in this experiment. The results showed that eggs from older (60 weeks of age) broiler breeders were heavier (p = 0.001) than those from younger (30 weeks of age) broiler breeder. In addition, older broiler breeder had larger (p = 0.001) embryos showing a higher yolk sac (p = 0.001) and higher gastrointestinal tract relative weight (p = 0.007) than those from younger broiler breeder. The activities of pancreatic lipase and trypsin enzymes were also higher in embryos from older broiler breeder than those from younger broiler breeder (p = 0.001 and p = 0.002, respectively). Nevertheless, at the seven-day-old chick, no difference was observed in relative weight of gastrointestinal tract or pancreatic lipase and trypsin activities between older and younger broiler breeder age. However chicks from older broiler breeder were heavier than those from younger broiler breeder (p = 0.005). These data suggest that broiler breeder age is important on grower and on the development of the gastrointestinal tract and pancreatic lipase and trypsin activities of embryo. However after one week of hatching the morphophysiological difference disappear.
Keywords: Broiler breeder age; Embryo; Enzymatic activity; gastrointestinal tract